Mid- to long-term results of single-stage surgery for patients with chronic osteomyelitis using a bioabsorbable gentamicin-loaded ceramic carrier. (1st September 2022) - McNally, Martin A.; Ferguson, Jamie Y.; Scarborough, Matthew; Ramsden, Alex; Stubbs, David A.; Atkins, Bridget L.
Abstract : Aims: Excision of chronic osteomyelitic bone creates a dead space which must be managed to avoid early recurrence of infection. Systemic antibiotics cannot penetrate this space in high concentrations, so local treatment has become an attractive adjunct to surgery. The aim of this study was to present the mid- to long-term results of local treatment with gentamicin in a bioabsorbable ceramic carrier. Methods: A prospective series of 100 patients with Cierny-Mader Types III and IV chronic ostemyelitis, affecting 105 bones, were treated with a single-stage procedure including debridement, deep tissue sampling, local and systemic antibiotics, stabilization, and immediate skin closure. Chronic osteomyelitis was confirmed using strict diagnostic criteria. The mean follow-up was 6.05 years (4.2 to 8.4). Results: At final follow-up, six patients (six bones) had recurrent infection; thus 94% were infection-free. Three infections recurred in the first year, two in the second year, and one 4.5 years postoperatively. Recurrence was not significantly related to the physiological class of the patient (1/20 Class A (5%) vs 5/80 Class B (6.25%); p = 0.833), nor was it significantly related to the aetiology of the infection, the organisms which were cultured or the presence of nonunion before surgery (1/10 with nonunion (10%) vs 5/90 without nonunion (5.6%); p = 0.570). Organisms with intermediate or high-grade resistance to gentamicin were significantly more likely in polymicrobial infections (9/21; 42.8%) compared with monobacterial osteomyelitis (7/79 (8.9%); p < 0.001). However, recurrence was not significantly more frequent when a resistant organism was present (1/16 for resistant cases (6.25%) vs 5/84 in those with a microbiologically sensitive infection (5.95%); p = 0.958). Conclusion: We found that a single-stage protocol, including the use of a high-delivery local antibiotic ceramic carrier, was effective over a period of several years. The method can be used in a wide range of patients, including those with significant comorbidities and an infected nonunion. Cite this article: Bone Joint J  2022;104-B(9):1095–1100.